Pengaruh E-Literacy terhadap Perencanaan Keuangan Generasi Z - Wa Ode Tri Artia; Agus Munandar (Jurnal Impresi Indonesia, 2025)
This study aims to analyze the influence of e-literacy on Generation Z's financial planning in Indonesia using a comparative literature study method. E-literacy consists of technical, evaluative, and strategic skills in accessing and utilizing digital information, which plays a crucial role in the financial behavior of the younger generation. This study shows that a high level of e-literacy significantly contributes to personal financial management, budgeting, consumer debt control, and Generation Z's investment skills. The results also indicate that e-literacy not only improves the efficiency of financial applications but also strengthens valid digital-based decision-making processes. The development of e-literacy is crucial in fostering Generation Z's financial resilience. Therefore, inclusive collaboration between the education sector, regulators, and digital technology players is needed. The power of e-literacy is a key factor in creating a young generation that is not only technologically savvy but also financially savvy.